Optimization of Organic/Water Hybrid Electrolytes for High‐Rate Carbon‐Based Supercapacitor. (9th August 2019) - Xiao, Dewei; Dou, Qingyun; Zhang, Li; Ma, Yalan; Shi, Siqi; Lei, Shulai; Yu, Haiyun; Yan, Xingbin
Abstract: "Water‐in‐salt" (WIS) electrolytes with wide electrochemical stability windows (ESWs) have made a breakthrough in energy density of aqueous batteries and supercapacitors (SCs), but the sluggish ion diffusion limits their widespread application. Although the ion diffusion of WIS electrolytes can be improved by the addition of organic co‐solvents, the effects of types and amounts of added organic solvents on the physicochemical properties of hybrid electrolytes are not clear. Here, the conductivity, ESW, and flammability of a series of hybrid electrolytes prepared by adding different organic solvents to a typical lithium bis(trifluoromethane sulfonyl) imide (LiTFSI)‐based WIS electrolyte are systematically studied. The results show that acetonitrile (ACN) is the best one to improve ion diffusion while maintaining high‐level safety and wide ESW. Furthermore, a ternary phase diagram of LiTFSI/H2 O/ACN is drawn to comprehensively show the relationship among the conductivity, flammability, and solubility of the hybrid electrolytes. According to the guidance of this phase diagram, an optimal hybrid electrolyte (LiTFSI/H2 O/(ACN)3.5 ) is obtained, and the carbon‐based symmetric SC using such hybrid electrolyte is able to fully work at 2.4 V with superior rate capability and excellent cycling stability over 40 000 cycles. Abstract : A ternary phase diagram to show the relationship among the conductivity, flammability, and solubility of organic/water hybrid electrolytes is drawn successfully, which can be used as the guidance to choose the best hybrid electrolyte for building a carbon‐based supercapacitor having high operation voltage and superior rate performance.